Evaluation, Criticism and Alternative Forms of the Development Models From a Historical Perspective: the Case of Turkey and Hungary - Gokdemir, Levent (Ekonomika, 2005)
In this study, firstly the macroeconomic situation and development problems of developing countries (Turkey and Hungary) will be presented by certain indicators. With a critical approach, traditional development models will be examined; alternative models that could contribute to solving the problems of developing countries, especially transition economies of Eastern Europe, will be explained and a stable development process for them will be outlined. In this respect, as a suggestion of solution, the state and the planning should be placed in the center of the economy.The main theme of this study is to criticize the traditional development models and to guide the developing countries by explaining the alternative development models.